2021
DOI: 10.1186/s13052-021-01013-8
|View full text |Cite|
|
Sign up to set email alerts
|

Inter-society consensus for the use of inhaled corticosteroids in infants, children and adolescents with airway diseases

Abstract: Background In 2019, a multidisciplinary panel of experts from eight Italian scientific paediatric societies developed a consensus document for the use of inhaled corticosteroids in the management and prevention of the most common paediatric airways disorders. The aim is to provide healthcare providers with a multidisciplinary document including indications useful in the clinical practice. The consensus document was intended to be addressed to paediatricians who work in the Paediatric Divisions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 134 publications
(185 reference statements)
1
8
0
1
Order By: Relevance
“…BTS guidelines encouraged the use of ICS in preschool children with one or more awakenings at night/week, or with symptoms, or use of SABA ≥ three times/week [ 29 ], whereas NICE guidelines recommend starting ICS if symptoms (nocturnal awakenings, cough) occurred three times per week or more [ 82 ]. The recent Italian intersociety consensus published in 2021, summarizing all these guidelines and recommendations, concluded that a trial with daily ICS is recommended in all preschool children with recurrent wheezing or with less frequent but severe exacerbations, regardless of the definitive diagnosis [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BTS guidelines encouraged the use of ICS in preschool children with one or more awakenings at night/week, or with symptoms, or use of SABA ≥ three times/week [ 29 ], whereas NICE guidelines recommend starting ICS if symptoms (nocturnal awakenings, cough) occurred three times per week or more [ 82 ]. The recent Italian intersociety consensus published in 2021, summarizing all these guidelines and recommendations, concluded that a trial with daily ICS is recommended in all preschool children with recurrent wheezing or with less frequent but severe exacerbations, regardless of the definitive diagnosis [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study by Brand and colleagues found that controller therapy with daily ICS reduced the risk of acute exacerbation over a 24-week period [ 86 ]. A recent Italian consensus on airway disease in children suggested that, when started, controller therapy should be continued for at least 3 months [ 83 ]. The same article reported that NICE 2017 guidelines suggested at least an eight-week trial with a moderate dose of ICS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correct diagnostic and therapeutic approaches to this condition require further investigations [2,3,5]. In such a scenario, due to the lack of firm evidence, a major role is acquired by experts' opinion, which can be addressed through consensus approaches, such as the Delphi Panel, a methodology increasingly used also in the field of pediatrics [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of RARS and CRS is controversial; several types of antibiotics have been used with limited results, since after initial improvement, patients eventually relapse [9,17]. Corticosteroid irrigations through the nasal passages and oral corticosteroids have also been used based on the few studies conducted in children with different results [1,[18][19][20]. Mucolytics, expectorants, and antihistamines have not been shown to be helpful [21,22].…”
Section: Introductionmentioning
confidence: 99%